Revolutionizing Children's English Vocabulary Acquisition: The Power of Games “My Talking Tom” - Supriatna, Nana; Muhria, Lanlan; Rofi’i , Agus (CV. Tripe Konsultan, 2024)
This study examines how interactive digital games, particularly